Microdeletions in 9q33.3-q34.11 in five patients with intellectual disability, microcephaly, and seizures of incomplete penetrance: is STXBP1 not the only causative gene?. Issue 1 (December 2015) - Ehret, Julia; Engels, Hartmut; Cremer, Kirsten; Becker, Jessica; Zimmermann, Johannes; Wohlleber, Eva; Grasshoff, Ute; Rossier, Eva; Bonin, Michael; Mangold, Elisabeth; Bevot, Andrea; Schön, Stefanie; et al.
Abstract Background Most microdeletions involving chromosome sub-bands 9q33.3-9q34.11 to this point have been detected by analyses focused onSTXBP1, a gene known to cause early infantile epileptic encephalopathy 4 and other seizure phenotypes. Loss-of-function mutations ofSTXBP1 have also been identified in some patients with intellectual disability without epilepsy. Consequently, STXBP1 is widely assumed to be the gene causing both seizures and intellectual disability in patients with 9q33.3-q34.11 microdeletions. Results We report five patients with overlapping microdeletions of chromosome 9q33.3-q34.11, four of them previously unreported. Their common clinical features include intellectual disability, psychomotor developmental delay with delayed or absent speech, muscular hypotonia, and strabismus. Microcephaly and short stature are each present in four of the patients. Two of the patients had seizures.De novo deletions range from 1.23 to 4.13 Mb, whereas the smallest deletion of 432 kb in patient 3 was inherited from her mother who is reported to have mild intellectual disability. The smallest region of overlap (SRO) of these deletions in 9q33.3 does not encompassSTXBP1, but includes two genes that have not been previously associated with disease, RALGPS1 andGARNL3. Sequencing of the two SRO genesRALGPS1 andGARNL3 in at least 156 unrelated patients with mild to severe idiopathic intellectual disability detected no causative mutations. Gene expression analyses in our patients demonstrated significantly reduced expression levels ofGARNL3, RALGPS1 andSTXBP1 only in patients with deletions of the corresponding genes. Thus, reduced expression ofSTXBP1 was ruled out as a cause for seizures in our patient whose deletion did not encompassSTXBP1. Conclusions We suggest that microdeletions of this region on chromosome 9q cause a clinical spectrum including intellectual disability, developmental delay especially concerning speech, microcephaly, short stature, mild dysmorphisms, strabismus, and seizures of incomplete penetrance, and may constitute a new contiguous gene deletion syndrome which cannot completely be explained by deletion ofSTXBP1 .